Service Quality and Perceived Value Toward Customer Satisfaction in E-Commerce Delivery: The Role of Trust - Chika Putri Nursalim; Tannia Tannia; Alexander Robert (AIBPM Publisher, 2025)
The rise of online shopping has transformed consumer behavior, shifting from traditional face-to-face transactions to digital purchasing through e-commerce platforms. This development has encouraged e-commerce companies to enhance the customer experience, including logistics services. However, issues such as delivery delays or damaged goods remain common problems. This study aims to examine the influence of service quality and customer perceived value on customer satisfaction in e-commerce delivery services, with customer trust as a mediating variable. A quantitative causal research design was used, involving 205 respondents residing in Jakarta who had shopped online and used e-commerce delivery services. Data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results indicate that service quality and customer perceived value significantly influence customer satisfaction. Customer trust also has a significant effect on satisfaction and serves as a full mediator between service quality and satisfaction, as well as between perceived value and satisfaction. These findings suggest that improving service responsiveness and delivery accuracy can enhance customer satisfaction through increased trust. E-commerce delivery providers are advised to focus on building trust by ensuring reliable and high-quality services.